The Islamic perspective on organ transplantation: case of eye transplantation - Shogar, Ibrahim (2021)
This Presentation introduces the audiences to the ethical implications of organ transplantation. Advancements in biomedical engineering has brought a great hope for new life or better to many helpless patients across the globe. however, organ transplantation also has posted many ethico legal questions. Form Islamic perspective organ transplantation can be viewed from three major dimensions i. The technical dimension (Restorative & Regenerative) ii. The philosophical dimension iii. The ethico legal dimension.